Assessment of Renal Function and Risk Factors for Chronic Kidney Disease in Patients With Peripheral Arterial Disease. (October 2017) - Jia, Xi-Bei; Hou, Xi-Hua; Ma, Qiu-Bo; Cai, Xiao-Wen; Li, Yi-Ran; Mu, Su-Hong; Na, Shi-Ping; Xie, Ru-Juan; Bao, Yu-Shi
Chronic kidney disease (CKD) and peripheral arterial disease (PAD) share common risk factors. We assessed renal function and the prevalence of CKD in patients with PAD and investigated the characteristics of the risk factors for CKD in this population. Renal function of 421 patients with PAD was evaluated. Among the participants, 194 (46.1%) patients had decreased estimated glomerular filtration rate (eGFR). The prevalence of CKD was much higher among patients with PAD. Hypertension (odds ratios [ORs] 2.156, 95% confidence interval [CI] 1.413-3.289, P < .001), serum uric acid (OR 3.794, 95% CI 2.220-6.450, P < .001), and dyslipidemia (OR 1.755, 95% CI 1.123-2.745, P = .014) were significantly associated with CKD and the independent risk factors for CKD in patients with PAD. CKD is common and has a high prevalence in a population with PAD. Patients with PAD may be considered as a high-risk population for CKD. Recognition and modification of risk factors for CKD might beneficially decrease CKD incidence and improve prognosis in patients with PAD.